Foundations and Applications of Mis A Model Theory Approach - Takahara, Yasuhiko; Liu, Yongmei; Klir, George J.; SpringerLink (Online service) (New York, NY : Springer New York, 2006)
Foundations and Applications of MIS presents a unique systems theory approach to management information system (MIS) development. The development is driven by the need to eliminate ambiguity in specification, design and construction of the application software. Further, the authors show that the considerable effort being expanded nowadays on validation, verification and testing, as required in current software engineering practices, will be reduced. The approach also reinforces the belief that MIS development is independent of software development. The work presents an approach that provides a theoretical foundation for MIS development from the systems theoretic viewpoint along with practical applications ranging from a transaction processing system to a solver system. Both formal systems theory and automatic system generation based on the authors' newly extended Prolog offer a significant increase in the efficiency of specification, design and production of the application software, as well as an increase in the functional reliability of the software produced. The book assumes a working knowledge of elementary set theory, logic, and familiarity with some systems concepts, such as the automaton model. Senior undergraduates and graduate students, researchers in management information systems, systems engineers and systems scientists will benefit from this book.
New Paradigm of Systems Development -- New Systems Development Methodology: The Model Theory Approach -- Model Construction Language and Systems Implementation Language -- Computer-Acceptable Set Theory for Model Construction -- Implementation Language: extProlog -- Model Theory Approach to Solver Systems Development -- Model Theory Approach to Solver System Development: Outlines -- User Model and Standardized Goal-Seeker -- Solver System Applications -- Traveling Salesman Problem: E-C-C Problem -- Regulation Problem: E-O-C Problem -- Linear Quadratic Optimization Problem: E-C-O and E-O-O Problems -- Cube Root Problem: I-C-C Problem -- Knapsack Problem: I-C-O Problem -- Class Schedule Problem: I-O-C Problem -- Data Mining Problem: I-O-O Problem -- Task Skeleton Model: Intelligent Data Mining System -- Model Theory Approach to Transaction Processing Systems Development -- Transaction Processing System on Browser-Based Standardized User Interface -- Browser-Based Intelligent Management Information System: Temporary Staff Recruitment System -- Database Connectivity for the Model Theory Approach -- Theoretical Basis for extProlog -- extProlog as Logic Programming Language -- Implementation of extProlog.
Keywords: Business; Business mathematics; Management information systems; Computer science; System theory; Mathematical models; Complexity, Computational; Business and Management; Business Mathematics; Mathematical Modeling and Industrial Mathematics; Management of Computing and Information Systems; Systems Theory, Control; Complexity; Electronic books